Microfluidic platform for screening the activity of immobilized photocatalysts for degradation of organic water pollutants - Roibu, Anca; Udroiu, Razvan; Dinu, Alexandru; Andronic, Luminita (ChemRxiv, 2024)
Photochemistry screening platforms have the potential to accelerate the discovery and development of new photocatalysts. This study presents the design and characterization of a novel activity screening platform of immobilized photocatalytic films for degrading water pollutants. The compact testing system is engineered with four 3D-printed microreactors and a rotative multi-wavelength LED light source, which is capable of emitting at the 395, 409, 413, and 443 nm. Despite the different LEDs being placed in a compact space, 95% of the light that reaches the photocatalytic films is emitted by the LEDs directly opposite them. Therefore, the design allows for a minimum of 16 distinct testing conditions by simply rotating the light source. The performance of the microfluidic platform was characterized using the photocatalytic degradation of a pesticide, imidacloprid, in the presence of P25 TiO2, immobilized as thin film on glass plates. The results demonstrated a consistent degradation efficiency of around 35 % at 395 nm, with negligible variation across the four microreactors and no influence of the testing order at 395, 409, 413 and 443 nm. Notably, the photocatalytic film activity did not decrease after 6 hours of operation and under five successive illumination conditions. The screening conditions were optimized using the dynamic water infusion which increased the degradation efficiency of the imidacloprid to 71 %. In addition, the dynamic illumination allowed the sequential operation of the 4 types of LEDs, and led to a halved degradation efficiency despite the LEDs were lighted up for only a quarter of the time. This microfluidic platform diminishes the manual labor and the quantities of photocatalyst and polluted water required per test compared to the batch screening, consequently, it emerging as an efficient and sustainable tool that is suitable for the automated screening of immobilized photocatalysts.
Keywords: Screening platform; Microfluidics; Photoreactors; Water treatment; Photocatalytic films